Cellular and Humoral Immune Responses to SARS-CoV-2 Vaccination in Inflammatory Bowel Disease Patients. (31st March 2022) - Cerna, Karin; Duricova, Dana; Hindos, Miroslav; Hindos Hrebackova, Jana; Lukas, Martin; Machkova, Nadezda; Hruba, Veronika; Mitrova, Katarina; Kubickova, Kristyna; Kastylova, Kristyna; Teplan, Vladimir; Lukas, Milan
Abstract: Background and Aims: Knowledge on the immunogenicity of anti-SARS-CoV-2 vaccines in inflammatory bowel disease [IBD] patients is limited. Therefore, SARS-CoV-2-specific T-cell responses and antibodies were analysed in 60 IBD vaccine recipients and 30 controls. Methods: SARS-CoV-2 IgG antibodies against the viral spike protein were measured at baseline and at 8 and 26 weeks after the second vaccine dose. SARS-CoV-2 IgG antibodies against the nucleocapsid antigens were measured at week 26. A SARS-CoV-2 interferon-gamma released assay [IGRA] was performed in all vaccinees at week 26. Results: At weeks 0 and 8, no differences were found in anti-spike antibodies between cohorts. At week 26, the decrease in antibody levels was more significant in the IBD cohort compared to the healthy cohort, and anti-nucleocapsid antibodies were not detected in either group. At week 26, 16 of 90 [18%] vaccinated individuals had a negative IGRA test result, seven of 90 [8%] were borderline and 67 [74%] had a positive IGRA result; 22 of the 23 individuals with negative or borderline IGRA results belonged to the IBD cohort. However, the overall functional ability of T-lymphocytes to produce interferon-gamma after the unspecific mitogen stimulation was lower in IBD patients. In vaccinated individuals with low or borderline IGRA, treatment with tumour necrosis factor-alpha inhibitors was the most frequent. In individuals with a significant drop in anti-spike antibody levels, plasmatic interferon-gamma concentrations after the specific SARS-CoV-2 stimulation were also insufficient. Conclusions: Simple humoral and cellular post-vaccination monitoring is advisable in IBD patients so that repeated vaccine doses may be scheduled.